Immunological reactions of rats to the transplantation of alginate microcapsules - Pasteur, I.P.; Baranova, L.A.; Dmytrukha, N.M.; Lahutina, O.S. (Reports of the National Academy of Sciences of Ukraine, 2017)
Transplantation of alginate microcapsules to rats leads to a number of immunological reactions, indicating the need for a further purification of commercial biopolymer before its use in experiments on animals.